Strengthening Public Trust through Zoning Policies in Student Admissions - Ahmad, Ahmad; Nengsi, Ratika; Asykur, Muamar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study evaluates the implementation of zoning policies in new student admissions (PPDB), especially its role in strengthening public trust in education policies. This study uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. Data analysis was carried out through three main stages: data reduction, data presentation, and verification, which refers to the Miles and Huberman approach. The study results indicate that the zoning policy has succeeded in increasing educational accessibility, especially for students from low socio-economic groups, with a more equitable distribution. However, technical challenges, such as limited technological literacy in the community and the need for more effective socialization, are still significant obstacles. Assistance posts in schools have proven to be an effective solution in increasing public understanding of this policy. Adjusting the zone radius based on school capacity is a strategic step to overcome the imbalance in the number of applicants. The implications of this study emphasize the importance of a multi-channel communication approach, strengthening community technological literacy, transparency in the implementation of education policies, and resources as considerations.